Development of a charge transfer space loop to improve adsorption performance in aerial electrostatic spray - Zhao, Denan; Lan, Yubin; Shen, Weiguo; Wang, Shizhou; Dixit, Abhishek (International Journal of Agricultural and Biological Engineering, 2020)
In order to solve the problem of insufficient adsorption rate of droplets on the target back via aerial electrostatic spray, this study proposed a high-voltage electrostatic generator to charge the liquids in two isolated water tanks with positive and negative charges respectively. A charge transfer loop was developed in space between the aerial electrostatic spray system and the ground. This method greatly enhanced the adsorption performance under outdoor conditions that 16.7% droplets density increased on the target front, a nearly fourfold destiny increased on the target back compared with the conventional UAV spray system. The target back-to-front ratio of droplet density was improved from 6.1% to 25.7%, which validated the satisfactory performance of the developed system.Keywords: aerial electrostatic spray, electrostatic adsorption, charge transfer loop, back deposition, droplet, developmentDOI: 10.25165/j.ijabe.20201305.5531Citation: Zhao D N, Lan Y B, Shen W G, Wang S Z, Dixit A. Development of a charge transfer space loop to improve adsorption performance in aerial electrostatic spray. Int J Agric & Biol Eng, 2020; 13(5): 50–55.